Catheter associated urinary tract infection in an acute care setting of a tertiary care centre in South India - Mishra, Debadutta; Rao, Kodukula Bhaskara (International Journal of Research in Medical Sciences, 2019)
Background: Catheter associated UTI is a serious cause of morbidity and mortality in intensive care unit (ICU) patients. Hence, authors undertook the present study to know the prevalence of catheter associated urinary tract infections (CAUTI) in medical ICU patients of tertiary care centre and to know the antibiotic resistance pattern of the causative organisms. Methods: A one-year prospective study was carried out from September 2015 to August 2016. Demographic data from the catheterized patients were collected daily and scrutinized for the signs and symptoms as per CDC criteria for confirmation as CAUTI. Relevant antimicrobial resistance data of etiologic agents were also collected to ascertain the prevalent resistance pattern. Results: The overall incidence of CAUTI was 14.69 per 1000 catheterized days in the present study. Out of the 37 diagnosed CAUTI cases, 12 (32.4%) were males and 25 (67.6%) were females with maximum patients being between 40 to 60 years of age. The commonest uropathogens was Escherichia coli (n=26) followed by K. pneumoniae (n=5). Both Escherichia coli and Klebsiella pneumoniae isolates were found to be 100% resistant to cefotaxime, ceftazidime and cefuroxime. Pseudomonas aeruginosa and Acinetobacter species were least common etiological culprits and demonstrated complete resistance to all the tested antibiotics. Conclusions: In the present study the prevalence of CAUTI is much higher which needs to be rectified by continuous monitoring and training of the staff in implementation of infection control practices in a proactive manner.